2017
DOI: 10.1371/journal.ppat.1006611
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated miR-146a transfer suppresses type I interferon response and facilitates EV71 infection

Abstract: Exosomes can transfer genetic materials between cells. Their roles in viral infections are beginning to be appreciated. Researches have shown that exosomes released from virus-infected cells contain a variety of viral and host cellular factors that are able to modulate recipient’s cellular response and result in productive infection of the recipient host. Here, we showed that EV71 infection resulted in upregulated exosome secretion and differential packaging of the viral genomic RNA and miR-146a into exosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 77 publications
4
127
0
Order By: Relevance
“…Besides, Hurwit and colleagues demonstrated that EBV LMP1 protein upregulated exosome secretion in the various cellular models related to EBV pathogenesis . Fu and colleagues showed that the EV71 infection results in an increased exosome release in THP‐1 and HT‐29 cells, as well as differential packaging of miR‐146a and the viral genomic RNA into exosomes. The exosomal EV71‐RNA genome can be transferred to a new target cell and replicates in these cells, while exosomal miR‐146a inhibits IFN‐I response in target cells, thereby facilitating the EV71 replication.…”
Section: Exosomal Mir‐146a In Viral Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, Hurwit and colleagues demonstrated that EBV LMP1 protein upregulated exosome secretion in the various cellular models related to EBV pathogenesis . Fu and colleagues showed that the EV71 infection results in an increased exosome release in THP‐1 and HT‐29 cells, as well as differential packaging of miR‐146a and the viral genomic RNA into exosomes. The exosomal EV71‐RNA genome can be transferred to a new target cell and replicates in these cells, while exosomal miR‐146a inhibits IFN‐I response in target cells, thereby facilitating the EV71 replication.…”
Section: Exosomal Mir‐146a In Viral Infectionmentioning
confidence: 99%
“…Since nonpermissive L929 cells do not express PSGL‐1 and SCARB2, it is suggested that exosomal EV71 RNA can overcome the limitation of the receptor for cellular entry, and mediate replication of the virus in a receptor‐independent manner. Of note, exosomal miR‐146a contributes to replicate exosomal EV71 RNA by suppressing IFN‐I response . In other viral infections or virus‐induced cancers, the role of exosomal miR‐146a in the modulation of the host immune system has not been studied, and further researches are needed.…”
Section: Exosomal Mir‐146a In Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs derived from EV71‐infected cells, for example, were preferentially enriched for miR‐146a, the miRNA that has been well‐documented to inhibit type I IFN responses (as described above). It was shown that the transfer of this miRNA in EVs resulted in suppression of type I IFN responses in recipient cells (Fu et al, ). In this report, the EVs were also found to contain the RISC proteins Argonaute 2 (AGO2) and GW182 and the authors suggest the transfer of the miRNA‐RISC complex might enable suppression of targets immediately after cell entry.…”
Section: Secreted Host Mirnas Promote Viral Infection and Contribute mentioning
confidence: 99%